Pengaruh Kompetensi Kerja Karyawan dan Komitmen Kerja Terhadap Kinerja - Haris Fauzi; Engkun Kurnadi; Neni Sri Nuraeni (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
This research began with the discovery of problems with employee performance. The problem seen in this research is employee performance that is capable of working competence and work commitment, where employees do not have good work skills and this is coupled with a low sense of employee loyalty when working. This research aims to determine the influence of work competency and work commitment on employee performance. The method used in this research is descriptive and verification analysis. The population in this study were employees of PT. Persada Selaras Indonesia, totaling 93 people, with a sample of all employees of PT. Persada Selaras Indonesia as many as 93 people. The sampling technique used is saturated sampling. Data collection techniques include observation, interviews, and distributing questionnaires. The analytical tools used in this research are classical assumption tests, multiple linear regression, coefficient of determination, model feasibility tests and partial hypothesis testing (t test). The results of this research show that work competency and work commitment have a positive and significant effect on employee performance at PT Persada Selaras Indonesia.